Mediating effect of technological innovation on the relationship between HRM, and performance in selected SMEs in Malaysia - Juhdi, Nurita; Hashim, Junaidah (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), Malaysia., 2018)
The study is to examine the relationship between Human Resource Management (HRM), technological innovation and firm performance among small and medium enterprises (SMEs) in Malaysia. The mediating effect of technological innovation on the relationship between HRM and firm performance was also measured. Data was collected by using survey technique to 165 SMEs that participated in the study. The correlation tests in this study indicated that all the variables are significantly related. The technological innovation was found giving partial mediating effect which signifies the importance of inculcating the spirit of technological innovation among SMEs (R2=.402, F=19.338, p<.01). The test also showed that technological innovation (ß=.328, p=.000) as the strongest predictor for firm performance and outweighed the explanatory power of the HRM practices. The findings also provide support to resource‐based theory and human capital theory.